2019
DOI: 10.1080/14756366.2019.1574779
|View full text |Cite
|
Sign up to set email alerts
|

Chemically stable inhibitors of 14-3-3 protein–protein interactions derived from BV02

Abstract: 14-3-3 are regulatory proteins that through protein-protein interactions (PPI) with numerous binding partners could be involved in several human diseases, including cancer, neurodegenerative disorders, and pathogens infections. Following our research interest in the development of 14-3-3 PPI inhibitors, here we exploited the privileged 4-aminoantipyrine scaffold in the design and synthesis of some derivatives endowed with antiproliferative activity against K-562 cells, and capable of binding to recombinant 14-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Our investigation demonstrates the underlying mechanism of hsa-miR-28-5p in the initiation and development of DLBCL. BV02 is a nonpeptide inhibitor of the 14-3-3/c-Abl protein-protein interaction, its bioactive form is phthalimide derivative 9, and inhibitors of 14-3-3 protein-protein interaction derived from BV02 are chemically stable [ 28 ]. Inosine monophosphate (IMP), pyridoxal phosphate (PLP), and the derivatives show inhibitory action of the 14-3-3/c-Abl PPI poorly [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation demonstrates the underlying mechanism of hsa-miR-28-5p in the initiation and development of DLBCL. BV02 is a nonpeptide inhibitor of the 14-3-3/c-Abl protein-protein interaction, its bioactive form is phthalimide derivative 9, and inhibitors of 14-3-3 protein-protein interaction derived from BV02 are chemically stable [ 28 ]. Inosine monophosphate (IMP), pyridoxal phosphate (PLP), and the derivatives show inhibitory action of the 14-3-3/c-Abl PPI poorly [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this issue, Corradi and his group used computational techniques, in combination with biophysical and biochemical techniques, to investigate a new set of promising hits with a stable scaffold at room temperature, while Iralde-Lorente and colleagues proposed a synthetic scheme of compound 14 and its chemically stable derivatives. These studies successfully identified two synthesizable and chemically stable compounds, BV01 (15) and 16 (Figure 8a) which showed antiproliferative activity against IM-resistant cells expressing the T315I Bcr-Abl mutation, and a K-562 erythroleukemia cell line at low micromolar concentrations, respectively [95,114]. Recently, a series of bivalent 14-3-3σ peptide inhibitors, 2a-d (17-20) (Figure 8b) were generated using on-resin stepwise substitution reactions on 1,3,5-triazine.…”
Section: Non-phosphonate-type Inhibitors Of 14-3-3σmentioning
confidence: 99%
“…The active cavity of 14-3-3 protein is used to recognize partner proteins. Some small inhibitors and stabilizers modulate the 14-3-3 protein function by targeting this active cavity ( Zhao et al, 2011 ; Iralde-Lorente et al, 2019 ; Gigante et al, 2020 ). Theoretically, K11 and K49, which are deeply located in the active pocket, can be bound to inhibit the activity of 14-3-3 σ.…”
Section: Resultsmentioning
confidence: 99%